Estimating Sovereign Credit Rating: Is Kuwait Overrated? Musaed S. AlAli (International Research in Economics and Finance, 2022)
Despite all the criticism surrounding the reliability of credit rating agencies’ rating systems, these agencies' ratings still play an essential role in determining the cost of funding for government bonds. These agencies are also accused of not applying the same standards for all countries resulting in mis-rating causing a disturbance in these countries economic and financial systems. Countries try their best to obtain the highest rating possible to reduce their cost of borrowing and increase the demand for their bonds in the global financial market. This research is set to examine whether or not Kuwait is getting a favorable sovereign credit rating from the three largest credit rating agencies. Using a panel data regression for 40 countries for the year 2017, results revealed that Kuwait enjoyed a favorable treatment from the three major credit rating agencies where it was rated by an average of 3.18 notches higher than what it should be. The results also indicates that Kuwait did not take advantage of its inflated credit rating and the policy makers did not address the factors that would improve their credit rating and as a result Kuwait sovereign credit rating was downgraded by all three credit rating agencies in